Hydrostratigraphic Evaluation using Lithological and Step-drawdown Test: A Case Study on the Aquifer of Ukhia, Cox's Bazar, Bangladesh - Hossain Khan, Mohammad Forrukh; Monir, Minhaj Uddin; Ahmed, Mohammad Tofayal; Hasan, Md Yeasir; Islam, Md Naim; Hasan, Md Mehedi; Akter, Rafica (The Dhaka University Journal of Earth and Environmental Sciences, 2022)
Hydrogeological studies on the aquifer of Ukhia, Cox's Bazar, Bangladesh, were performed using well logs and step-drawdown tests to evaluate the aquifer's condition. In two recent boreholes (WDZ.8E.04 and WDZ.8E.02), the impacts of four single-well stepdrawdown experiments were studied using Jacob and Rorabaugh's technique. The lithological data analysis of boreholes has indicated that the aquifer in the investigated area is from the early Miocene and consists of upper and middle Boka Bil Formations. Step-drawdown test results showed well losses ranging from 17% to 19.8%, with aquifer losses ranging from 82.6% to 80.2% in two wells, indicating improved efficiency. Specific capacity values ranged from 18.13 m3/day/m to 23.79 m3/day/m for two wells, whereas well-efficiency values ranged from 95.3% to 98.5%, indicating that wells are well planned and installed. The estimated aquifer transmissivity varied from 271.24 m2/day to 263.3 m2/day as measured by wells, exhibiting higher production of water from the tube wells. The existence of aquifer/well-face laminar flow is indicated in the studied area, showing that turbulent flow is negligible. The water-bearing area accumulates a large amount of water. The entire lithological and pumping test approach outlines the successful application of single-well to step-drawdown tests and predicts future safe and sustainable groundwater from well on higher production. The Dhaka University Journal of Earth and Environmental Sciences, Vol. 10(3), Special Issue 2022: 53-62